The Effect of Experimentally Induced Maternal Hypothyroidism on Gfap and S100B Protein Expression in Fetal Brain Tissue on Tenth and Fifteenth Gestational Days and in Newborn Period - Donder, Emir; Ozkan, Yusuf; Gencer, Vedat; Baydas, Giyaseddin (Ortadogu Ad Pres & Publ Co, 2010)
Objective: Thyroid hormone is very important in central nervous system development. Thyroid hormone deficiency in critical periods of central nervous system causes maturation delays in glial cells and neurons. It is well known that maternal hypothyroidism causes psychomotor and mental retardation in the offspring. Thyroid hormones have important functions in survival, division and differentiation of both neuronal and glial precursor cells. It was reported that S100B and glial fibrillar acidic protein (GFAP) were good markers showing astrocyte maturation. S100B and GFAP levels were found to be lower in astrocyte maturation defects. There are many trials on to the effect of maternal hypothyroidism on central nervous system development, but there are few on the effect of maternal hypothyroidism on glial proteins. The effect of maternal thyroid hormones on glial proteins is not known during pregnancy. We aimed to evaluate the effect of maternal hypothyroidism on glial fibrillar acidic protein and S100B protein expression, and consequently astrocyte maturation in fetal brain on 10, 15(th) gestational days and in newborn period. Material and Methods: Fifteen experimentally hypothyroid rats and 15 normal rats (control group) were included in this experimental study. Both groups were divided into three subgroups as 10, 15(th) gestational days and newborn. S100B and glial fibrillar acidic protein levels were studied in the brains of fetuses on 10(th), 15(th) gestational days and in newborns by Western Blot method. Results: S100B protein and glial fibrillar acidic protein levels were found significantly lower in brain tissues of hypothyroid mothers' offsprings when compared to the control group. Conclusions: Our study showed that maternal hypothyroidism might cause changes in GFAP and S100B protein expression. These changes may indicate astrocyte maturation retardation.
Gebelik döneminde oluşturulan deneysel hipotiroidinin onuncu, on beşinci gestasyonel gün ve yenido?andaki fetal beyin dokusunda GFAP ve S100B protein ekspresyonuna etkisi
Keywords: Glial fibrillary acidic protein; thyroid hormones